The Strategic Role of Orphanages in the Formation of Foster Children’s Religious Values - Rismawati, Yanda; Mukmin Ridoan Simamora; Faizah Kamila; Hidayah Yanti (Dirasah: Jurnal Pendidikan Islam, 2025)
Children who grow up in orphanages often face significant challenges in the development of religious values due to the absence of a family environment that ideally serves as the foundation for moral and spiritual formation. In this context, orphanages are expected to assume a strategic role in shaping the religious character of foster children. This study aims to analyze how orphanages contribute to the internalization of Islamic values among children under their care. Employing a descriptive qualitative approach, data were gathered through in-depth interviews with caregivers, non-participant observation of religious activities, and informal interactions with foster children. The results indicate that orphanages actively nurture religious values through structured programs such as Qur’anic memorization (tahfidz), regular Qur’anic recitation (tilawah), congregational prayers, Islamic studies sessions, and participation in religious commemorations. Caregivers play a crucial role by serving as moral and spiritual role models and by fostering daily religious habits such as prayer, polite language, and respectful behavior. These efforts help build a stable spiritual rhythm and a sense of religious identity in the children’s daily lives. However, the study also reveals limitations in personal emotional support due to the limited number of caregivers, which hinders affective engagement with all children equally. Despite this challenge, the findings underscore the strategic function of orphanages not only as social welfare institutions but also as non-formal educational settings that play a critical role in forming the religious identity of foster children. The study highlights the importance of combining structural programs with consistent emotional support to ensure holistic religious development